إنعكاسات العولمة على ظاهرة الفقر في البلدان النامية ( الأردن ومصر – حالة دراسية ) (المجلة العراقية للعلوم الاقتصادية, 2018)
This study aims at analyzing the main contemporary challenges that faced the under developed countries Presented by globalization and its impacts on poverty phenomenon by using several indices such as inflation Rate,unemployment, average growth of product ,per capita income ,per capita expenditure on health and Education as a ratio of GDP andFDI as a ratio of GDP . The hypothesise adopted in this study is that globalization in its various aspects has negative impacts on Poverty phenomenon in underdeveloped countries.The paper divided into two sections . the first one deals with theoretical framework ofpoverty indicators. The second section studies the indicators of poverty phenomenon in Jordan and Egypt according to a set Of indicators and show their impacts on the average poverty in those countries . Finally ,some conclusions And recommendations were reached .